Studies in Ancient Greek Dialects : From Central Greece to the Black Sea. - Giannakis, Georgios (Trends in classics. Supplementary volumes., 2017)
A new collective volume with over twenty important studies on less well-studied dialects of ancient Greek, particularly of the northern regions. The book covers geographically a broad area of the classical Greek world ranging from Central Greece to the overseas Greek colonies of Thrace and the Black Sea. Particular emphasis is placed on the epichoric varieties of areas on the northern fringe of the classical Greek world, including Thessaly, Epirus and Macedonia. Recent advances in research are taken into consideration in providing state-of-the art accounts of these understudied dialects, but also of more well-known dialects like Lesbian. In addition, other papers address special intriguing topics in these, but also in other dialects, such as Thessalian, Lesbian and Ionic, or focus on important multi-dialectal corpora such as the oracular tablets from Dodona. Finally, a number of studies examine broader topics like the supraregional Doric koinai or the concept of dialect continuum, or even explore the possibility of an ancient Balkansprachbund, which included Greek too. This new reference work covers a gap in current research and will be indispensable for people interested in Greek dialectology and ancient Greek in general.